CONCEPTUAL APPROACHES TO MODELING CONTINUOUS ENVIRONMENTAL EDUCATION (Pedagogy of Higher and Secondary Education, 2007)
The system of continuous ecological éducation is one the most important directions in the éducation of XXI century. It is directed to the development of students’ abilities, satisfaction of their interests and need in a professional détermination and growing.